Descriptive study to assess the awareness of ill effects of consanguineous marriage on pregnancy, fetus and child in antenatal mothers - Surendrakumar, Dhipikasri; Murugan, Rajalekshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Consanguinity refers to marriage or a reproductive relationship between two closely related individuals. Consanguinity may significantly impact the occurrence of autosomal recessive conditions and congenital anomalies. The degree of relatedness between two individuals defines the proportion of genes shared between them. Hence this study was planned to assess the awareness level, the association between awareness level and education, association between awareness level of and socioeconomic class. Methods: Direct interview through a self-structured questionnaire containing questions about demographic details, awareness of participants was conducted among (n=100) antenatal mothers attending SMC-OBG, OPD using convenient sampling. Knowledge of ≥50% is considered adequate. Data entry and analysis done using SPSS 16.0 software. Descriptive statistics were calculated for background variables like socio-demographic characteristics. p value less than 0.05 were considered to be statistically significant. Results: 54% have an educational qualification above high school. 58% belonged to the lower socioeconomic strata. 67% had adequate knowledge. Out of the 26 people who have had consanguineous marriage, 30.8% have 2’ consanguinity, 69.2% have 3’ consanguineous marriage. Participants having educational status above high school have 1.7 times more knowledge than lesser educational qualification. People of higher socioeconomic status have 3.2 times more knowledge than lower socioeconomic status. Association between knowledge with socioeconomic status is significant. Conclusions: The target population has divergent attitudes towards consanguinity, though the awareness was decently high among many of them. Strategies to disseminate information in school programmes should be taken into consideration. Couples in consanguineous relationships can be identified, provided with information about their risk and, if needed referred for genetic counselling.